The Quality Analysis Of Sambal Masin (Sumbawa Specialties) With Variation Concentrations Of Salt And Tamarind - Asmawati Asmawati; Jumisayati Jumisayati; Adi Saputrayadi (Agrikan: Jurnal Agribisnis Perikanan, 2020)
Masin is a type of chili sauce fermented by using rebon shrimp with the addition of salt and tamarind widely consumed in the West Nusa Tenggara, being particularly popular among the Sumbawa people. The aimed of this research was to determine the effect of salt and tamarind concentration on the quality of masin as the Sumbawa sauce. The experiment was conducted using a completely randomized design (CRD) with salt and tamarind concentration. The treatments were MU1 (8% salt: 10% tamarind), MU2 (salt 10 %: 8% tamarind), MU3 (12% salt: 6% tamarind), MU4 (14% salt: 4% tamarind), and MU5 (16% salt: 2% tamarind). Data was analyzed using Co-Stat software with 5% significance differences. The treatments that were significantly different was then analyzed using Honestly Significance Difference (HSD). The results showed that the treatment of salt and tamarind concentrations significantly affected the water content, protein content, acidity (pH) of the color, aroma, and masin flavor of Sumbawa. The best treatments was obtained at MU4 (14% salt: 4% tamarind) with 6% acidity (pH), 69.35% water content, 11.54% protein content, 4.45 (reddish-brown) color value score. Aroma 3.75 (like) and taste 3.55 (somewhat like)